Estimating the Economic Value and Determining Factors of Unused Medicines Among Households in Cibarusah District, Bekasi Regency - Rozak, Abdul; Priyanto, Priyanto; Khaira Rusdi, Numlil (Media Farmasi: Jurnal Ilmu Farmasi, 2025)
The accumulation of unused and expired medicines in households poses significant economic, health, and environmental challenges. This study aimed to estimate the economic value of unused medicines and identify factors contributing to their accumulation among households in the Cibarusah District, Bekasi Regency, Indonesia. A cross-sectional survey was conducted from May to June 2025 involving 354 households selected using a convenience sampling approach. Data were collected through structured, face-to-face interviews with validated questionnaires and analyzed descriptively using Microsoft Excel 2021 and SPSS version 29. Results showed that 71.5% of households stored unused medicines, representing an estimated total economic value of IDR 25,271,179, or an average loss of IDR 99,886 per household. Expired medicines accounted for 28.5% of all stored items, with a mean value of IDR 114,897 per household. Analgesics, antipyretics, nonsteroidal anti-inflammatory drugs (NSAIDs), and antigout agents were the most frequently stored drug classes (20.1%), followed by gastrointestinal medicines (15.2%). The primary reasons for medicine accumulation were recovery from illness (70.9%), drug ineffectiveness (15.8%), and expiration (28.5%). Most respondents were female (67.2%), aged 36–55 years, and had completed secondary education. When extrapolated to all 32,515 households in Cibarusah District, the potential economic loss due to unused medicines reached approximately IDR 1.18 billion. This study highlights the substantial economic burden associated with household medicine storage and the need for improved public awareness of rational medicine use. Strengthening educational programs, involving community pharmacists in household medicine management, and establishing structured medicine take-back systems are essential to reduce pharmaceutical waste and its economic impact. These findings contribute valuable local evidence to support national strategies for promoting sustainable and responsible medicine use in Indonesia.